Constructing a composite indicator to assess cyclical systemic risks: An early warning approach - Heidi Koponen (Bank of Finland, 2024)
The main contribution of this paper is the construction of a cyclical systemic risk indicator from early warning indicators of banking crises (EWIs) used in Finland. Previous research has shown that combining EWIs can enhance their early warning properties. This study evaluates the indicator's performance through AUROC and noise-to-signal ratios and finds that the early warning performance of the composite indicator is good (AUROC of 0.76), with a low noise-tosignal ratio (0.2). The indicator warns of an approaching crisis well beforehand and the precrisis level of the indicator seems to correlate with the severity of the crisis. The study also examines the impact and relative importance of individual EWIs within the composite indicator by analysing the performance of the composite indicator when individual EWIs are excluded. Results suggest that including an external balance indicator is crucial, while excluding the credit-to-GDP gap (also called Basel gap) has minimal effect on the indicator's performance. The limited usefulness of the Basel gap can be attributed to its redundancy, as it shares substantial similarities with other indicators, resulting in minimal influence on the composite indicator's performance.
URN:NBN:fi-fe2024040214214
Keywords: G01; G17; E44; E47; 330; financial cycles; systemic risk; banking crises; early warning systems